An Improved Model for the Heat‐Up Stage of the CAS‐OB Process: Development and Validation. Issue 10 (4th July 2018) - Kärnä, Aki; Järvinen, Mika; Sulasalmi, Petri; Visuri, Ville‐Valtteri; Ollila, Seppo; Fabritius, Timo
Abstract : Details of chemical heating in the CAS‐OB process are not known exactly, making a computational model valuable in process development and control. A phenomena‐based numerical model of the CAS‐OB heating stage is presented. Chemical equilibrium at reaction surfaces is assumed to be limited by mass transfer. Making use of a law of mass action based kinetic approach, reactions, and mass transfer rates are solved simultaneously. Computational fluid dynamics is used to derive heat and mass transfer coefficients, which are then used in our model, consisting of only a few computational nodes. The model includes steel melt, slag, and gas phases, bell, and ladle structures, and three reaction fronts. Radiation, conduction, and convection heat transfer are solved in the system. The model outputs temperatures and chemical composition of the system, and the results are validated with industrial data from two measurement campaigns. Abstract : A numerical model for the heating stage of the CAS‐OB process is presented. The model utilizes results from CFD simulations in a process model written in c++. Chemical reactions and energy conservation are calculated as a function of time.